CAN ENVIRONMENT, SOCIAL AND GOVERNMENT DISCLOSURE INCREASE FINANCIAL PERFORMANCE ? - Majidi, Lalu; Wahyuningtyas, Endah Tri (Universitas Nahdlatul Ulama Surabaya, 2024)
This study analyzes the effect of ESG disclosure on financial performance in mining companies listed on the Indonesia Stock Exchange. The data used in this study are secondary data, which are taken from annual reports and sustainability reporting in 2015-2020. The analytical tool used to test the hypothesis is multiple regression analysis with spss. ESG score use csrhub data. Contributions for practitioners and policy makers. Researchers suggest a special setting where the relationship between ESG activities and corporate financial performance will be positive and significant. These results are very useful for policy makers who seek to increase the active participation of companies in ESG activities. Community, Employee, Environment, Goverment and ESG variables simultaneously have a significant effect on financial performance, while partially the Community, Employee, Environment, Goverment variables have no significant effect on financial performance and the ESG variable has a positive and significant effect on financial performance.